2018
DOI: 10.1002/ppul.24170
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the yield of gastrointestinal testing in pediatric patients in aerodigestive clinic

Abstract: Objective To improve understanding of the interrelatedness of airway and esophageal diagnoses by evaluating the yield of procedural and radiographic testing of the gastrointestinal tract in children with airway conditions by their referring diagnoses in a pediatric aerodigestive clinic. Methods A retrospective chart review of all 325 patients seen in the aerodigestive program from 2010 to 2013 was performed in a single academic medical center. Demographics and results from esophagogastroduodenoscopies with bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Aksglaede calculated a specificity of 100% and a sensitivity of 52% for UGI (compared to 24-h pH monitoring) [ 12 ]. For UGIs, DeBoer et al published a sensitivity of 47.3%, specificity 74.2%, and positive predictive value of 50%, but there was no information given on either technique or provocative maneuver use (in particular, whether a water-siphon test was performed) [ 13 ]. Thompson et al demonstrated in their study of 117 patients that UGIs detect unprovoked, spontaneous GER in only 26% of ph-monitoring–positive patients.…”
Section: Gastroesophagel Reflux: Clinical and Functional Assessmentmentioning
confidence: 99%
“…Aksglaede calculated a specificity of 100% and a sensitivity of 52% for UGI (compared to 24-h pH monitoring) [ 12 ]. For UGIs, DeBoer et al published a sensitivity of 47.3%, specificity 74.2%, and positive predictive value of 50%, but there was no information given on either technique or provocative maneuver use (in particular, whether a water-siphon test was performed) [ 13 ]. Thompson et al demonstrated in their study of 117 patients that UGIs detect unprovoked, spontaneous GER in only 26% of ph-monitoring–positive patients.…”
Section: Gastroesophagel Reflux: Clinical and Functional Assessmentmentioning
confidence: 99%
“…Thirty‐six percent of aerodigestive EGDs are histologically abnormal, including esophagitis, gastritis, EoE, and duodenitis (27). Children with EA could develop EoE at a younger age (28).…”
Section: Diagnostics Approaches To Opdmentioning
confidence: 99%
“…Implementation of culture directed antibiotics prior to or during open airway reconstruction surgery can therefore improve outcomes. Studies have demonstrated that specific subsets of aerodigestive patients are more likely to have abnormal mucosal histology on upper GI endoscopy and/or abnormal impedance pH testing[ 22 , 23 ]. This includes those with previously diagnosed asthma, feeding difficulty, and esophageal atresia with or without tracheoesophageal fistula, with 40%-50% yield on upper GI testing[ 22 ].…”
Section: Aerodigestive Program Servicesmentioning
confidence: 99%
“…Studies have demonstrated that specific subsets of aerodigestive patients are more likely to have abnormal mucosal histology on upper GI endoscopy and/or abnormal impedance pH testing[ 22 , 23 ]. This includes those with previously diagnosed asthma, feeding difficulty, and esophageal atresia with or without tracheoesophageal fistula, with 40%-50% yield on upper GI testing[ 22 ]. Findings noted included reflux esophagitis and EoE.…”
Section: Aerodigestive Program Servicesmentioning
confidence: 99%